Experimental evolution of Vibrio cholerae identifies hypervesiculation as a way to increase motility in the presence of polymyxin B - Giacomucci, Sean; Mathieu-Denoncourt, Annabelle; Vincent, Antony T.; Jannadi, Hanen; Duperthuy, Marylise (Frontiers in Microbiology, 2022)
Vibrio cholerae is the bacterium responsible for the cholera disease and a natural inhabitant of aquatic environments. V. cholerae possesses a unique polar flagellum essential for motility, adhesion, and biofilm formation. In a previous study, we showed that motility and biofilm formation are altered in the presence of subinhibitory concentrations of polymyxin B in V. cholerae. In this study, we performed an experimental evolution to identify genes restoring the motility in the presence of a subinhibitory concentration of polymyxin B. Mutations in 5 genes have been identified in 3 variants derived from 2 different parental strains A1552 and MO10: ihfA, vacJ (mlaA), mlaF, dacB and ccmH. We further demonstrated that the variants derived from MO10 containing mutations in vacJ, and in mlaF and dacB secrete more and larger membrane vesicles that titer the polymyxin B, which is expected to limit its impact on the bacterial envelope and to participate in the flagellum retention and motility.